Salivary protein changes in response to acute stress in medical residents performing advanced clinical simulations: a pilot proteomics study. (19th May 2017) - Marvin, Rachel K.; Saepoo, Muncharie B.; Ye, Simiao; White, Donald B.; Liu, Rong; Hensley, Kenneth; Rega, Paul; Kazan, Viviane; Giovannucci, David R.; Isailovic, Dragan
Abstract: Context: Quantitative changes of salivary proteins due to acute stress were detected. Objective: To explore protein markers of stress in saliva of eight medical residents who performed emergency medicine simulations. Materials and methods: Saliva was collected before the simulations, after the simulations, and following morning upon waking. Proteins were separated by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), identified by mass spectrometry (MS), and relatively quantified by densitometry. Results: Salivary alpha-amylase and S–type cystatins significantly increased, while the ∼26 kDa and low-molecular weight (MW) (<10 kDa) SDS-PAGE bands exhibited changes after stress. Discussion and conclusion: Alpha-amylase and cystatins are potential salivary markers of acute stress, but further validation should be performed using larger sample populations.